2011
DOI: 10.1007/s11250-011-9856-7
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of GnRH administration on the ovarian response and laparoscopic intrauterine insemination of Awassi ewes treated with eCG to induce superovulation

Abstract: The effect of GnRH administration on superovulatory response of ewes treated with equine chorionic gonadotrophin (eCG) in breeding and nonbreeding seasons and the contribution of laparoscopic insemination to the improvement of fertilization and embryo recovery were investigated. Twenty-four nonpregnant Awassi ewes of 3-4 years of age were randomly allocated into two groups (n = 12). Each ewe was treated with a progesterone impregnated intravaginal sponge for 12 days. The following superovulation treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In a study conducted by Casali et al (2017), it is reported that an average of 57 animals per hour were inseminated by laparoscopy, leading to 1 min required at least for each ewe to be inseminated. In the study performed by Azawi and Al-Mola (2011), a similar time (5 min on average) was required for laparoscopic intrauterine insemination, which resembles the mean duration of the procedure as found in our study. Pau et al (2019) proposed an innovative techniques which include surgery of ovine cervical folds in order to facilitate the following cervical cannulation and uterine insemination.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In a study conducted by Casali et al (2017), it is reported that an average of 57 animals per hour were inseminated by laparoscopy, leading to 1 min required at least for each ewe to be inseminated. In the study performed by Azawi and Al-Mola (2011), a similar time (5 min on average) was required for laparoscopic intrauterine insemination, which resembles the mean duration of the procedure as found in our study. Pau et al (2019) proposed an innovative techniques which include surgery of ovine cervical folds in order to facilitate the following cervical cannulation and uterine insemination.…”
Section: Resultssupporting
confidence: 83%
“…Moreover, in case of accidental vessel rupture and haemorrhage, abdominal cavity is already exposed and emergency haemostasis is easier. Azawi and Al-Mola (2011) state that laparotomic technique is poorly applied due to decreased fertility of animals which undergo this procedure. In our study, using a minimally invasive laparotomic method, ewes were naturally bred in the following reproductive season but no decreased PR was noticed (90%).…”
Section: Resultsmentioning
confidence: 99%
“…GnRH can be useful to synchronize and ensure ovulation (Azawi & Al‐Mola, 2011; Balaro et al, 2016; Reyna et al, 2007). A single dose of GnRH given 24–36 h after removal of the progestagen pessary synchronizes the LH peak approximately 40 h after pessary withdrawal and ovulation occurs in 90% of ewes within 72 h after pessary withdrawal (Menchaca & Rubianes, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…An extensive body of literature has shown that gonadotropin hormone‐releasing hormone (GnRH) can be useful to synchronize and ensure ovulation in farm animal reproduction (Azawi & Al‐Mola, 2011; Balaro et al, 2016; Gonźalez‐Bulnes et al, 2004; Menchaca & Rubianes, 2004; Reyna et al, 2007). A single dose of GnRH given 24 to 36 h after removal of the progestagen pessary synchronizes the luteinizing hormone peak approximately 40 h after pessary removal and ovulation occurs in 90% of ewes within 72 h after pessary removal (Menchaca & Rubianes, 2004).…”
Section: Introductionmentioning
confidence: 99%